1996
DOI: 10.1093/jnci/88.21.1550
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lung Cancer and for Intervention Effects in CARET, the Beta-Carotene and Retinol Efficacy Trial

Abstract: CARET participants receiving the combination of beta-carotene and vitamin A had no chemopreventive benefit and had excess lung cancer incidence and mortality. The results are highly consistent with those found for beta-carotene in the Alpha-Tocopherol Beta-Carotene Cancer Prevention Study in 29133 male smokers in Finland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
530
2
23

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,120 publications
(566 citation statements)
references
References 29 publications
11
530
2
23
Order By: Relevance
“…In contrast to the results of many observational studies and the current meta‐analysis, two large randomized controlled trials (RCT's), the ATBC and CARET, showed an increased risk of lung cancer with high‐dose supplemental β ‐carotene among smokers 14, 15, 16. The increased risk at high doses may be related to the prooxidant activity of β ‐carotene when administered as a supplement in high doses (5–10 times greater than normal dietary intake) to heavy smokers 6, 45, 46.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In contrast to the results of many observational studies and the current meta‐analysis, two large randomized controlled trials (RCT's), the ATBC and CARET, showed an increased risk of lung cancer with high‐dose supplemental β ‐carotene among smokers 14, 15, 16. The increased risk at high doses may be related to the prooxidant activity of β ‐carotene when administered as a supplement in high doses (5–10 times greater than normal dietary intake) to heavy smokers 6, 45, 46.…”
Section: Discussioncontrasting
confidence: 91%
“…By contrast, two large randomized double‐blind placebo‐controlled trials, the alpha‐tocopherol‐ β ‐carotene (ATBC) and the β ‐carotene and Retinol Efficacy Trial (CARET) showed an increased risk of lung cancer among high‐risk people supplemented with high doses of β ‐carotene and/or α ‐tocopherol 13, 14, 15, 16.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a result, the genetic make-up of participants in supplementation trails may influence the outcome of such trials. Therefore genetics may be a factor, along with differences in environmental stress, lifestyle behaviour and Se intake, that contributes to differences in study populations that could explain why micronutrient supplementation trials, including those with Se, have been disappointing or contradictory (see, for example (4)(5)(6)(7)(8)(9) ). The identification of genetic differences in micronutrient metabolism may useful in improving the design of future supplementation trials.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, results of antioxidant supplementation trials have largely been disappointing, demonstrating little effect of Se and vitamins E and C on gastric cancer [180] and no effect of vitamin E and β-carotene on the prevention of heart disease [181]. Some randomized, controlled trials have actually displayed adverse effects of supplementation with antioxidants such as β-carotene and vitamins E or A on lung cancer and heart disease [118,182,183], demonstrating a need for caution. In other trials, the results have been mixed: Se supplementation correlated with an increased risk of some cancers and a reduced risk of others [173].…”
Section: History Of Clinical Trials Of Antioxidants In Other Diseasesmentioning
confidence: 99%